Anti-Candida auris activity in vitro and in vivo of micafungin loaded nanoemulsions. (25th November 2022) - Marena, Gabriel Davi; Carvalho, Gabriela Corrêa; dos Santos Ramos, Matheus Aparecido; Chorilli, Marlus; Bauab, Tais Maria
Abstract: Fungi are becoming increasingly resistant, especially the new strains. Therefore, this work developed nanoemulsions (NE) containing micafungin (MICA), in order to improve its action against infections caused by Candida auris . The NEs were composed of the surfactants polyoxyethylene (20) cetyl ether (Brij 58 ® )/soy phosphatidylcholine at 10%, sunflower oil/cholesterol at 10%, and 80% PBS. The NEs were characterized by Dynamic Light Scattering (DLS). For the microbiological in vitro evaluation the determination of the minimum inhibitory concentration (MIC), ergosterol/sorbitol, time kill and biofilms tests were performed. Additionally, the antifungal activity was also evaluated in a Galleria mellonella model. The same model was used in order to evaluate acute toxicity. The NE showed a size of ∼ 42.12 nm, a polydispersion index (PDI) of 0.289, and a zeta potential (ZP) of −3.86 mV. NEM had an average size of 41.29 nm, a PDI of 0.259, and a ZP of −4.71 mV. Finally, both nanoemulsions showed good stability in a storage period of 3 months. Although NEM did not show activity in planktonic cells, it exhibited action against biofilm and in the in vivo infection model. In the alternative in vivo model assay, it was possible to observe that both, NEM and free MICA at 0.2 mg/l, was effective against the infection, being that NEM presented a better action. Finally, NEM and free MICA showed no acute toxicity up to 4 mg/l. NEM showed the best activities in in vitro in mature antibiofilm and in alternative in vivo models in G. mellonella . Although, NEs showed to be attractive for MICA transport in the treatment of infections caused by C. auris in vitro and in vivo studies with G. mellonella, further studies should be carried out, in mice, for example. Lay Summary: Candida auris is a fungus that can cause infections in the human body. As it is a microorganism with a high potential for resistance, it is extremely important to develop new therapeutic alternatives. Thus, nanotechnology, the science that studies materials with extremely small sizes, can be considered a promising method in the treatment of these infections.